Ocular exposure to blue-enriched light has an asymmetric influence on neural activity and spatial attention - O'CONNELL, REDMOND (My University, 2016)
Brain networks subserving alertness in humans interact with those for spatial attention orienting. We employed blue-enriched light to directly manipulate alertness in healthy volunteers. We show for the first time that prior exposure to higher, relative to lower, intensities of blue-enriched light speeds response times to left, but not right, hemifield visual stimuli, via an asymmetric effect on right-hemisphere parieto-occipital α-power. Our data give rise to the tantalising possibility of light-based interventions for right hemisphere disorders of spatial attention
PUBLISHED
Keywords: spatial attention orienting; spatial attention orienting